(untitled) (Journal of Dhaka National Medical College & Hospital, 2013)
Objective: This study was undertaken to determine whether short term bladder catheterization would be more beneficial than the routinely practiced long term catheterization after vaginal hysterectomy for prolapsed uterus. Materials and methods: This randomized controlled trial was conducted in Obstetrics and Gynecology Department of Dhaka National Medical College Hospital from January 2009 to January 2011. A total of 106 women were included in this study. They were randomized into short term catheterization group where transurethral catheter was removed after 24 hours of surgery and long term catheterization group where catheter was removed on 3rd post operative day. Result: Mean time of first voiding after removal of catheter was almost equal in both groups (2.82±1.42 hours and 2.74±1.52 hours). Duration of catheter did not affect the duration of first voiding time after removal of catheter (P>0.05). None of the women had residual volume of urine >200 ml in both groups. Mean residual volume is significantly high in long term catheterization group (P<0.05). Urinary tract infection was also significantly high in long term catheterization group (P<0.05) and majority of the infection were caused by E. coli. Conclusion: Short term catheterization is more beneficial in terms of lower incidence of urinary tract infection and prevention of bladder over filling as compared to long term catheterization after vaginal prolapsed surgery. DOI: http://dx.doi.org/10.3329/jdnmch.v18i2.16012 J. Dhaka National Med. Coll. Hos. 2012; 18 (02): 4-8